Language teaching for young learners (John Benjamins Publishing Company, 2019)
"An academic, refereed journal, which publishes articles relating to the teaching and learning of foreign / second languages for young learners. 'Young' is defined as including both children and adolescents. Although some young learners receive language instruction in out-of-school contexts, in the main the journal publishes articles reporting on teaching languages in state and private elementary and secondary school contexts. This journal publishes articles about a range of foreign/second languages - not just English." -- from journal website.